FEATURES OF DEVELOPMENT OF SMALL BUSINESS IN STAVROPOL REGION - Galina Marakhovskaya; Victoriya Germanova (Вестник Северо-Кавказского федерального университета, 2022)
This article summarizes the contemporary trends of development of small business in Stavropol region, shows the main economic indicators of activity of small enterprises. The authors identified negative features of the current stage of business development, including the growth of the size of the shadow economy. Described alternative tax regimes for small enterprises, noted the inconsistency of tax policy and examples of negative consequences of increasing the tax burden. For elimination of the revealed shortcomings it is proposed a combination of tax administration and measures of state support of small business while maintaining the current tax burden.